Source Code Comprehension and Appropriation by Novice Programmers: Understanding Novice Programmers’ Perception about Source Code Reuse - Müller, Luana (2019)
Software development practices rely extensively on reusing source code written by other programmers. One of the recurring questions about such practice is how much programmers, acting as users of somebody else’s code, really understand the source code that they inject it in their programs. The question is even more important for novices, who are trying to learn what programming is and how it should be practiced on a larger scale. In this paper we present the results of an ongoing research using a semiotic approach to investigate how novice programmers reuse source code, and how, through messages inscribed in the source code of the programs they write or reuse, they communicate, implicitly or explicitly, what such source code "means" to them and others. We carried out three studies with novice programmers, and results suggest that source code reuse may impact what programmers take their source code to mean.